Predictive control applied to 5DPO - RoboCup middle-size omnidirectional robots - António Paulo Moreira (2007)
- This paper presents a nonlinear model basedpredictive controller (NMPC) for trajectory tracking of theMiddle-size Omnidirectional Robots from the 5DPO RoboticSoccer team. The strategy proposed uses methods of numericaloptimization to perform real time nonlinear minimization ofthe cost function. The cost function penalizes the robot positionerror, the robot orientation angle error and the control effort.Experimental results of the trajectories following and theperformance of the methods of optimization are presented.